Existence and actuality: Hartshorne on the ontological proof and immanent causality - Gómez Alonso, Modesto M. (Logos. Anales del Seminario de Metafísica, 2013)
In this paper, our objectives are: (i) To provide an outline of the modal version of the ontological proof proposed by Charles Hartshorne, one version which emphasizes the unique logical properties of the notion of God, which demonstrates that the proof leaves open only two coherent alternatives, positivism and modal theism, and which, in order to cope successfully with positivism, appeals to a process philosophy inspired by Whitehead which accepts contingent properties, as well as essential ones, in God. (ii) To evaluate Hartshorne’s position, defending it against some usual misunderstandings and suggesting some improvements, in concrete, an assessment of Russell’s project of reducing modal values to scope-words, and the development of an iterative conception of modality. (iii) To vindicate Hartshorne’s philosophical attitude, a circumspect rationalism which tries to make sense of recalcitrant phenomena without yielding to epistemological or conceptual deflationism, and which underlines that experience has a rational basis, but that reason cannot exhaust experience.
Keywords: Abstract-concrete paradox; Actuality; Existence; Hartshorne; Immanent Causality; Logical space; Positivism; Unconditional necessity